The Role of Startups in Structural Transformation - Dent, Robert C.; Karahan, Fatih; Pugsley, Benjamin; Şahin, Ayşegül (American Economic Review, 2016)
The U.S. economy has been going through a striking structural transformation–the secular reallocation of employment across sectors–over the past several decades. We propose a decomposition framework to assess the contributions of various margins of firm dynamics to this shift. Using firm-level data, we find that at least 50 percent of the adjustment has been taking place along the entry margin, due to sectors receiving different shares of startup employment than their employment shares. The rest is mostly due to life cycle differences across sectors. Declining overall entry has a small but growing effect of dampening structural transformation.